Symposium 3: Approaches to Developing a Theoretical Understanding of Networked Learning: From personal inquiry to generic coding - Mann, Sarah; Chappel, Helen; McAteer, Erica; Harris, Rachel; Marsden, Sally; Tolmie, Andy; Lally, Vic; Tickner, Sue (Proceedings of the International Conference on Networked Learning, 2002)
The purpose of this symposium is to provide an opportunity to engage in a discussion of theoretical frameworks for understanding and methodologies for representing and investigating the nature of networked learning, grounded in instantiations of practice and experience of studying, teaching and researching networked learning. The symposium brings together the work of four different researchers in this area, all of whom are developing their understanding of networked learning through analysis of networked learning interactions and/or from experiential accounts of participating in networked learning. Specific aspects focused on: methodology; theoretical frameworks; learner and tutor experience; communication for learning; and participation in networked learning communities. Papers: Fast Coding of On-line Learning Behaviours using an ‘Elements’ Approach Helen Chappel, Erica McAteer, Rachel Harris, Sally Marsden CHARACTERISING ON-LINE LEARNING ENVIRONMENTS Erica McAteer, Andy Tolmie, Rachel Harris, Helen Chappel, Sally Marsden, Vic Lally Understanding Networked Learning: A Personal Inquiry into an Experience of Adult Learning On-line Sarah Mann Charting Change in Networked Learners: What can we learn about what they learn? Sue Tickner